Η διάγνωση εκπαιδευτικών αναγκών (ΔΕΑ) στο πλαίσιο της φιλοσοφίας της συμμετοχής - Σιδηρά, Βιβή; Ναγόπουλος, Νίκος Ι. (Adult Education Critical Issues, 2025)
This article focuses on the identification of educational needs in the educational process within participatory philosophy. It is one of the processes that make up the educational process at individual and group level. It is designed, implemented, evaluated and updated based on the development of educational needs. Learning incorporates change while respecting diversity, whether it concerns the whole or a part of it. Educational needs include explicit educational needs, but also underlying and hidden educational needs that are not clearly expressed (Amu Centre Copenhagen, 1992). The components that constitute such needs relate to characteristics, knowledge, skills and abilities, weaknesses and expectations, limitations and desires. At methodological level participatory observation, case studies, role-play, project work, interviews, workshops, etc. are used. Educational needs are also investigated during the assessment as they may be subjects, priority areas or even criteria of evaluation. The findings of the evaluation feed new or existing data back into the identified educational needs. Factors influencing the identification of educational needs are the time available, the internal educational policy of VET organizations, the appropriately qualified workforce, the existing know-how, participatory assessment, educational roles and relations, the group dynamics, the current institutional framework, etc.